2022
DOI: 10.1093/carcin/bgac051
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphic variant in telomere maintenance is associated with worrisome features and high-risk stigmata development in IPMNs

Abstract: Intraductal papillary mucinous neoplasms (IPMNs) are non-obligatory precursor lesions of pancreatic ductal adenocarcinoma (PDAC). The identification of molecular biomarkers able to predict the risk of progression of IPMNs toward malignancy is largely lacking and sorely needed. Telomere length (TL) is associated with the susceptibility of developing cancers, including PDAC. Moreover, several PDAC risk factors have been shown to be associated with IPMN transition to malignancy. TL is genetically determined, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Thus, the results suggest the absence of a shared genetic background between PDAC risk and IPMN progression. This conclusion agrees with our previous results, which identified a germline variant associated with clinical IPMN progression that is not associated with PDAC risk ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the results suggest the absence of a shared genetic background between PDAC risk and IPMN progression. This conclusion agrees with our previous results, which identified a germline variant associated with clinical IPMN progression that is not associated with PDAC risk ( 33 ).…”
Section: Discussionsupporting
confidence: 93%
“…Several lines of evidence suggest that lifestyle and genetic factors play a role in transforming IPMN into PDAC ( 32 36 ). Since carcinogenesis is a complex and multifactorial process, the only viable way to predict individuals’ risks is to analyse them with a comprehensive approach ( 33 , 34 ). Additionally, it has been proposed that PDAC risk factors may play a role in IPMN progression.…”
Section: Introductionmentioning
confidence: 99%
“… 73 Multiple genes, such as RTEL1 , LRRC31 , TERF1 , TERT , ATM , PXK , ACYP2 , POT1 , and CTC1 , can influence TL through SNPs, which are the most common form of stable genetic variation in the genome. 34 , 35 , 36 , 37 , 39 , 74 , 75 , 76 , 77 , 78 Studies have shown that LTL is affected by clinical, lifestyle, and risk factors, but these factors alone cannot explain variations in LTL. TL-related genetic variants may affect LTL and cancer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is genetically determined by single nucleotide polymorphisms (SNPs) using 11 variants alone or combined [acylphosphatase 2 (ACYP2)-rs11125529, PX serine/threonine kinase (PXK)-rs6772228, telomerase ribonucleic acid (RNA) component (TERC)-rs10936599, nuclear assembly factor 1 ribonucleoprotein (NAF1)-rs7675998, telomerase reverse transcriptase (TERT)-rs2736100, oligonucleotide/oligosaccharide-binding fold containing 1 (OBFC1)-rs9420907, CST telomere replication complex component 1 (CTC1)-rs3027234, zinc finger protein 208 (ZNF208)-rs8105767, zinc finger protein 676 (ZNF676)-rs412658, DEAH-box helicase 35 (DHX35)-rs6028466, zinc finger and BTB domain containing 46 (ZBTB46)-rs755017] that affect telomere length (teloscore). This teloscore showed no association with progression to pancreatic cancer, except the PXK-rs6772228-A variant that had an increased risk of such progression [ 28 ].…”
Section: Genomic Profiling – Molecular Alterationsmentioning
confidence: 99%